2013
DOI: 10.1007/s40145-013-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fracture toughness using the area of micro-crack tracks left in brittle materials by Vickers indentation test

Abstract: Abstract:In this article, a new method has been presented for the estimation of fracture toughness in brittle materials, which enjoys improved accuracy and reduced costs associated with fracture toughness testing procedure compared to similar previous methods, because a vast range of specimens with irregular cracks can be accommodated for testing. Micron-sized alumina powders containing 0.05 wt% magnesium oxide (MgO) nanoparticles were mixed and also together with 2.5 vol%, 5 vol%, 7.5 vol%, 10 vol%, and 15 vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 34 publications
3
68
0
Order By: Relevance
“…It was observed that the microcraks generated by Vickers indentation occur after a critical load has been reached and depending on the type of coating and indentation direction they usually propagate on the directions of the indent diagonals. This mechanism of propagation of microcracks appears usually in homogeneous materials and in particular, in brittle materials [3], [8], [9]. Generally, after the Vickers indentation two types of microcracks can be generated, described as Half-penny cracks (median/radial cracks) or Palmqvist cracks (radial cracks) (Fig.2b), where l is the average length of the cracks, a is the half average length of the diagonal and c is the sum of l and a.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…It was observed that the microcraks generated by Vickers indentation occur after a critical load has been reached and depending on the type of coating and indentation direction they usually propagate on the directions of the indent diagonals. This mechanism of propagation of microcracks appears usually in homogeneous materials and in particular, in brittle materials [3], [8], [9]. Generally, after the Vickers indentation two types of microcracks can be generated, described as Half-penny cracks (median/radial cracks) or Palmqvist cracks (radial cracks) (Fig.2b), where l is the average length of the cracks, a is the half average length of the diagonal and c is the sum of l and a.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…To distinguish between these two types of cracks, it can be applied a criterion based on the ratio of cracks length/diagonal indentation [9]. A general rule admits that if c/a ≥ 2, the model is the type Half-penny and if c/a < 2, the model is Palmqvist [3]. Other authors assert that the cracks are Palmqvist type only if 0.25 ≤ l/a ≥ 2.5 [10] and they are Half-penny only if c/a ≥ 2.5 [11].…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations